Mast Cell-Derived Exosomes Promote Th2 Cell Differentiation via OX40L-OX40 Ligation. (15th March 2016) - Li, Fei; Wang, Yuping; Lin, Lihui; Wang, Juan; Xiao, Hui; Li, Jia; Peng, Xia; Dai, Huirong; Li, Li
Abstract : Exosomes are nanovesicles released by different cell types, such as dendritic cells (DCs), mast cells (MCs), and tumor cells. Exosomes of different origin play a role in antigen presentation and modulation of immune response to infectious disease. In this study, we demonstrate that mast cells and CD4 + T cells colocated in peritoneal lymph nodes from BALB/c mouse. Further, bone marrow-derived mast cells (BMMCs) constitutively release exosomes, which express CD63 and OX40L. BMMC-exosomes partially promoted the proliferation of CD4 + T cells. BMMC-exosomes significantly enhanced the differentiation of naive CD4 + T cells to Th2 cells in a surface contact method, and this ability was partly inhibited by the addition of anti-OX40L Ab. In conclusion, BMMC-exosomes promoted the proliferation and differentiation of Th2 cells via ligation of OX40L and OX40 between exosomes and T cells. This method represents a novel mechanism, in addition to direct cell surface contacts, soluble mediators, and synapses, to regulate T cell actions by BMMC-exosomes.